Деятельность историко-просветительского общества «Мемориал» в Южной Украине во второй половине 80-х – начале 90-х гг. ХХ века - Михайлов, В. В.; Mikhailov, V. V. (My University, 2013)
RU: В статье на основе документов областных государственных архивов и материалов периодических изданий Украины рассматривается деятельность неформальных общественных организаций по ликвидации «белых пятен» национальной истории. Раскрыт процесс становления и функционирования историко- просветительского общества «Мемориал» в Южной Украине во второй половине 1980-х – начале 1990-х гг. Определен вклад общества «Мемориал» в формирование украинского демократического движения накануне распада СССР и образования независимой Украины. EN: The article, basing on the Ukrainian regional state archives documents and periodicals materials, considers informal public organizations activity on ―blank spots‖ liquidation in the national history. The process of the historical-enlightening society "Memorial" formation and functioning in Southern Ukraine in the second half of the 1980s – at the beginning of the 1990s is revealed. The contribution of the society ―Memorial‖ to the formation of the Ukrainian democratic movement on the eve of the USSR collapse and the formation of independent Ukraine is determined.
Historical-enlightening society “memorial” activity in southern ukraine in the second half of the 80s – at the beginning of the 90s of the XXth century
Keywords: неформальное движение; общество «Мемориал»; процесс реабилитации; историко-просветительская деятельность; Южная Украина; informal movement; society "Memorial"; process of rehabilitation; historical-enlightening activity; Southern Ukraine